STUDI PERBANDINGAN HASIL BELAJAR MATIMATIKA SISWA MENGGUNAKAN STRATEGI BELAJAR AKTIF THE POWER OF TWO DENGAN STRATEGI BELAJAR AKTIF GROP TO GROP PADA KELAS XI SMA NEGERI 12 KERINCI TAHUN PELAJARAN 2019/2020 - Lona Alika; Al Ikhlas; Jon Hendri; Ahmadi Zubir (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research was conducted at SMA Negeri 12 Kerinci. Based on the results of observations, there is still no perfect strategy applied by a teacher in the learning process. Learning is still centred on the teacher (Teacher-Centered) and student activity in learning is still lacking, students generally listen, pay attention, take notes and do the tasks given by the teacher. This causes students' mathematics learning outcomes to not be achieved optimally. One of the efforts made to improve students' ability to learn mathematics is through the power of two active learning strategy. This strategy requires all students in each team to be active so that it can have an impact on better learning outcomes. Based on the background, the following problems can be formulated: Are the mathematics learning outcomes of students using the power of two active learning strategy higher than the learning outcomes of students using the grop to grop active learning strategy in class X SMA Negeri 12 Kerinci in the 2019/2020 academic year. The purpose of this study was to determine the comparison of students' mathematics learning outcomes using the power of two active learning strategy with the grop to grop active learning strategy in class XI SMA Negeri 12 Kerinci in the 2019/2020 academic year. This research is an experimental research. The population in this study consisted of 3 (three) classes totalling 83 people. Furthermore, of the three classes, two classes will be taken as samples, withdrawing samples using random sampling techniques, so that the selected experimental class I is class XA totalling 28 people, who use the power of two active learning strategy and experimental class II is class XC 28 people, who use the active learning strategy grop to grop. The data in this study were taken from the final test scores. For hypothesis testing, the t-test formula was used. From the analysis results obtained tcount = 0.929 and ttable = 1.673. Thus, tcount> ttable so the hypothesis H0 is rejected and the hypothesis H1 is accepted. It is concluded that the mathematics learning outcomes of students taught with the power of two active strategy are higher than the mathematics learning outcomes of students using the grop to grop active learning strategy.